Carbon-fluorine chain modified carbon-based hydrophobic electrocatalytic CO2 reduction catalyst as well as preparation method and application thereof

By introducing hydroxyl groups on the surface of carbon nanotubes, loading molecular catalysts and performing silane hydrophobic modification, carbon-based hydrophobic electrocatalysts were prepared, which solved the problem of easy loss of hydrophobicity of existing carbon-based catalysts and achieved high efficiency and stability CO2 reduction catalytic performance.

CN119433614AActive Publication Date: 2025-02-14ZHEJIANG UNIV
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202411566919.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-05
Publication Date
2025-02-14
Estimated Expiration
2044-11-05

AI Technical Summary

Technical Problem

Existing carbon-based catalysts are prone to loss of hydrophobicity in electrocatalytic CO2 reduction reactions, resulting in degradation of catalytic performance and poor stability.

Method used

By introducing hydroxyl groups on the surface of the carbon nanotubes and loading the molecular catalyst cobalt phthalocyanine (CoPc), then sonicating in DMF solvent, followed by hydrophobic modification in aqueous silane solution, a carbon-fluorochain modified carbon-based hydrophobic electrocatalyst is formed.

Benefits of technology

The hydrophobicity and stability of the catalyst are significantly improved, efficient catalytic performance is maintained, CO2 mass transfer resistance is reduced, reaction current density is improved, and the preparation process of catalyst ink is simplified.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119433614A_ABST
    Figure CN119433614A_ABST
Patent Text Reader

Abstract

The invention relates to an electro-catalysis CO2 reduction catalyst, in particular to a fluorocarbon chain modified carbon-based hydrophobic electro-catalysis CO2 reduction catalyst as well as a preparation method and application thereof, and belongs to the technical field of electro-catalysis. The method comprises the following steps: S1, heating a carbon nano tube at the temperature of 400 to 500 DEG C for 0.5 to 1.5 hours to remove impurities contained in the carbon nano tube; s2, carrying out oxidation treatment on the carbon nanotubes to introduce hydroxyl groups; s3, carrying out ultrasonic treatment on the oxidized carbon nanotube obtained in the step S2 in a solvent DMF environment so as to load the molecular catalyst; and S4, carrying out hydrophobic modification on the oxidized carbon nanotubes loaded with the molecular catalyst in the S3 in a silane aqueous solution by using silane. Through a covalent bond connection strategy, a fluorocarbon chain of silane with excellent hydrophobicity is stably anchored on the surface of the carbon nanotube, so that the problems that the hydrophobicity of a catalytic electrode prepared from an existing carbon-based catalyst is easy to lose, the catalytic performance is easy to reduce, the stability is not high and the like in a reaction are solved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to an electrocatalytic CO2 reduction catalyst, in particular to a carbon-fluorine chain modified carbon-based hydrophobic electrocatalytic CO2 reduction catalyst, a preparation method and application thereof, belonging to the technical field of electrocatalysis. Background Art

[0002] The increasing consumption of fossil raw materials has brought about serious climate problems. The emission and utilization of CO2 has become an important topic in current scientific research and industrial applications. The electrocatalytic CO2 reduction reaction (CO2RR) has received widespread attention as a method of converting CO2 into high-value chemical raw materials or fuels using renewable energy. The electrocatalytic carbon dioxide reduction reaction can use renewable energy to convert carbon dioxide into high-value chemical raw materials or fuels. When performing CO2RR at industrially relevant current densities, it is crucial to ensure the hydrophobicity of the electrocatalytic electrode in order to achieve efficient catalytic activity and stable reaction processes. Hydrophobic electrodes help improve the gas transport of CO2 and ensure that the CO2 reactants can reach the catalytic active sites smoothly.

[0003] At present, in order to explore the influence of hydrophobic environment on the selectivity and stability of CO2RR, various research teams have explored different hydrophobic methods and continuously optimized the methods. Wakerley et al. published a research result entitled "Bio-inspired hydrophobicity promotes CO2 reduction on a Cu surface" in Nature Materials, preparing a copper electrode with a hydrophobic dendritic structure. The hydrophobic surface can significantly increase the local CO2 concentration on the catalyst surface, and increase the Faraday efficiency of ethylene from 9% of the hydrophilic electrode to 56% of the ethylene Faraday efficiency; Chang et al. published a research work entitled "Ionomers Modify the Selectivity of Cu-Catalyzed Electrochemical CO2 Reduction" in ChemSuschem, reporting that the addition of ionomers will change the hydrophilicity of the electrode and significantly change the selectivity of the Cu catalyst. At various current densities, hydrogen is the main product of the hydrophilic Cu / PTP catalytic electrode.

[0004] Carbon-based materials are widely used in the preparation of CO2RR catalysts due to their good electrical conductivity, large specific surface area, and high chemical stability. However, conventional carbon-based materials often have poor hydrophobicity. In the actual preparation of catalytic electrodes, in order to maintain the hydrophobicity of the catalytic electrodes, it is often necessary to add additional hydrophobic materials such as PTFE particles. However, due to the possible shedding of hydrophobic materials during the reaction, the hydrophobicity of the electrode is usually reduced, which in turn affects the catalytic performance of the catalyst. Summary of the invention

[0005] The purpose of the present invention is to provide a carbon-fluorine chain modified carbon-based hydrophobic electrocatalytic CO2 reduction catalyst to solve the problems of the catalytic electrode prepared by the existing carbon-based catalyst that the hydrophobicity is easily lost during the reaction, the catalytic performance is easily reduced, and the stability is not high.

[0006] The technical solution adopted by the present invention to solve its technical problem is:

[0007] A method for preparing a carbon-based hydrophobic electrocatalytic CO2 reduction catalyst modified by a carbon-fluorine chain, the method comprising the following steps:

[0008] S1, heating the carbon nanotubes at a temperature of 400-500°C for 0.5h-1.5h, cooling to room temperature, washing after purification by acid washing, and freeze-drying to remove impurities contained in the carbon nanotubes;

[0009] S2, heating the carbon nanotubes obtained by the pretreatment in S1 in a mixed solution of concentrated sulfuric acid, sodium nitrate and potassium permanganate with a mass concentration of 96-98% to perform oxidation treatment on the carbon nanotubes to introduce hydroxyl groups, washing and freeze-drying;

[0010] The oxidation treatment temperature is not higher than 45°C;

[0011] S3, subjecting the oxidized carbon nanotubes obtained by the treatment in S2 to ultrasonic treatment in a DMF solvent environment to load the molecular catalyst, washing, and freeze-drying;

[0012] The molecular catalyst is cobalt phthalocyanine (CoPc) or nickel phthalocyanine;

[0013] S4, hydrophobically modifying the oxidized carbon nanotubes loaded with molecular catalysts in S3 with silane in a silane aqueous solution, heating to 45°C-120°C for 2h-4h, centrifugally washing to remove unreacted reagents, and freeze-drying to obtain a carbon-fluorine chain-modified carbon-based hydrophobic electrocatalytic CO2 reduction catalyst (CoPc MDE-Si);

[0014] Preparation of silane aqueous solution: silane content is 1wt% to 10wt%, the solvent is a mixture of ethanol and water in a mass ratio of 1 to 2:1, and the silane and solvent are mixed and hydrolyzed for 1 to 6 hours;

[0015] The mass ratio of the oxidized carbon nanotubes to silane is 10:1 to 60:1.

[0016] Preferably, the mass ratio of the oxidized carbon nanotubes to the silane is 15 to 25: 1. When the silane is selected from 1H, 1H, 2H, 2H-perfluorodecyltriethoxysilane, the mass ratio of the oxidized carbon nanotubes to the silane is optimally 20:1.

[0017] In the present invention, the carbon nanotubes may be single-walled carbon nanotubes or multi-walled carbon nanotubes. Single-walled carbon nanotubes (SWCNTs) are formed by curling a single layer of graphene; multi-walled carbon nanotubes (MWCNTs) are formed by concentrically curling multiple layers of graphene, which are not specifically limited here.

[0018] Preferably, the acid washing step S1 is to heat the carbon nanotubes in a 4-8 mol / L hydrochloric acid solution at 130-150° C. for 2 h to 3 h. The acid washing is to remove metal impurities or other residues that may be contained in the carbon nanotubes, and the acid washing can effectively improve the purity and quality of the carbon nanotubes.

[0019] Preferably, the reaction temperature for oxidizing the carbon nanotubes to introduce hydroxyl groups in S2 is 40-45°C.

[0020] Preferably, the silane includes one or more of 1H, 1H, 2H, 2H-perfluorodecyltriethoxysilane, 1H, 1H, 2H, 2H-perfluorododecyltrichlorosilane, (3, 3, 3-trifluoropropyl)trimethoxysilane, 1-(trimethylsilyl)heptafluoropropane, 3, 3, 3-trifluoropropylmethyldimethoxysilane, propyltrimethoxysilane or hexadecyltrimethoxysilane. Preferably, 1H, 1H, 2H, 2H-perfluorodecyltriethoxysilane is used.

[0021] Preferably, in S4, heating is performed at 40-50°C for 2-3h, maintained at 70-80°C for 10-20min, and heated to boiling and maintained for 20-40min to promote sufficient grafting of silanol groups. The best conditions are heating at 48°C for 2.5h, maintained at 75°C for 15min, and heated to boiling and maintained for 30min.

[0022] Preferably, the process of introducing hydroxyl groups by oxidation treatment in S2 is: stirring the carbon nanotubes obtained by purification pretreatment in 96-98% concentrated sulfuric acid at room temperature overnight; adding sodium nitrate when the above solution is heated to 40°C-45°C; slowly adding potassium permanganate while keeping the reaction temperature below 45°C; the amount ratio of carbon nanotubes: 96-98% concentrated sulfuric acid: sodium nitrate: potassium permanganate is 1g: 20ml-23ml: 280mg-420mg: 0.8g-1.2g; then continue stirring at 40°C-44°C, add appropriate amount of water intermittently, stop heating after the reaction is sufficient, and add appropriate amount of water and hydrogen peroxide to the system to terminate the reaction. The amount ratio of carbon nanotubes: 96-98% concentrated sulfuric acid: sodium nitrate: potassium permanganate is preferably 1g: 20ml-23ml: 350mg: 1g. According to the inventors' multiple experiments, the degree of oxidation of carbon nanotubes will affect the amount of modified silane, and the dosage ratio of carbon nanotubes, 96-98% concentrated sulfuric acid, sodium nitrate, and potassium permanganate is very critical. Increasing the degree of oxidation can introduce more hydroxyl groups on the surface of carbon nanotubes, thereby grafting more silane groups and improving the hydrophobicity of silane-modified carbon nanotubes; however, excessive oxidation will damage the graphite structure of carbon nanotubes, reduce their conductivity and the loading amount of molecular catalysts, thereby affecting the catalytic performance.

[0023] A carbon-fluorine chain modified carbon-based hydrophobic electrocatalytic CO2 reduction catalyst according to the present invention.

[0024] A use of the carbon-fluorochain modified carbon-based hydrophobic electrocatalytic CO2 reduction catalyst described in the present invention in the preparation of catalyst ink.

[0025] An application of the carbon-fluorine chain modified carbon-based hydrophobic electrocatalytic CO2 reduction catalyst in the preparation of a working electrode. The working electrode is mainly used in the field of electrocatalytic CO2 reduction to prepare CO.

[0026] Compared with the prior art, the present invention has the following beneficial effects:

[0027] 1. The present invention uses a covalent bond connection strategy to firmly anchor the carbon-fluorine chain of silane with excellent hydrophobic properties on the surface of carbon nanotubes. This bonding method can greatly improve the hydrophobicity of the prepared catalyst, and the hydrophobicity can still maintain a high degree of stability during the reaction. By selecting the type of grafted silane, the hydrophobicity of the hydrophobically modified carbon nanotubes is regulated; by enhancing the hydrophobicity of the catalyst surface, the present invention effectively maintains the structural stability of the three-phase interface (gas-liquid-solid) that is crucial in the catalytic process, and effectively prevents the electrolyte from invading the Wiener pore structure of the electrode, thereby avoiding the occurrence of electrode flooding due to excessive infiltration of the electrolyte.

[0028] 2. The present invention forms a dense and stable hydrophobic barrier on the surface of carbon nanotubes, effectively suppressing the common water flooding phenomenon in the electrocatalytic process, ensuring the transmission process of CO2 inside the electrode during the reaction, and reducing the mass transfer resistance of CO2. Therefore, it can effectively improve the catalytic performance of the electrode, achieve a significant increase in the reaction current density, and provide strong technical support for realizing efficient and sustainable electrochemical conversion processes.

[0029] 3. The modified catalyst prepared by the present invention exhibits significant simplified efficiency in the preparation process of catalyst ink, and the dispersibility and stability of the catalyst in the ink are significantly enhanced, thereby reducing the complexity of the formulation. This improvement helps to simplify the production steps and improve the consistency and quality of the product, which has positive significance for large-scale industrial production. BRIEF DESCRIPTION OF THE DRAWINGS

[0030] Figure 1 This is a flow chart of the carbon nanotube purification (a), carbon nanotube oxidation (b), carbon nanotube loading with molecular catalyst (c), and hydrophobic modification of carbon nanotubes (d) in the preparation method described in Example 1;

[0031] Figure 2 is the SEM image of the oxidized carbon nanotubes;

[0032] Figure 3 This is a SEM image of carbon nanotubes loaded with molecular catalysts and hydrophobically modified;

[0033] Figure 4 The catalytic performance of carbon nanotube molecular catalysts without and with hydrophobic modification at different current densities;

[0034] Figure 5 The carbon nanotube molecular catalysts without and with hydrophobic modification are shown in Figure 1 at 100 mA / cm 2 stability under

[0035] Figure 6 (a) Contact angle results and (b) catalytic performance of carbon nanotube molecular catalysts modified with different silanes;

[0036] Figure 7 The catalytic performance of carbon nanotube molecular catalysts with different oxidation degrees and hydrophobic modifications at different current densities. DETAILED DESCRIPTION

[0037] The technical solution of the present invention is further described in detail below through specific embodiments. It should be understood that the implementation of the present invention is not limited to the following embodiments, and any form of modification and / or change made to the present invention will fall within the protection scope of the present invention.

[0038] In the present invention, unless otherwise specified, all parts and percentages are by weight, and the equipment and raw materials used can be purchased from the market or are commonly used in the art. The methods in the following embodiments are all conventional methods in the art unless otherwise specified.

[0039] Unless otherwise specified, the reagents used in the following examples can be purchased from conventional biochemical reagent stores.

[0040] YLS-30T carbon paper, i.e., carbon paper substrate for fuel cell gas diffusion layer, is commercially available.

[0041] Nafion ionomer, aqueous solution is Nafion TM The polymer dispersant is Nafion 117 solution (McLean N831951 Nafion 117 perfluorinated resin solution, 5% in a mixture of lower aliphatic alcohols and water), Cas No.: 31175-20-9, commercially available.

[0042] Example 1

[0043] A method for preparing a carbon-based hydrophobic electrocatalytic CO2 reduction catalyst modified by a carbon-fluorine chain, comprising the following specific steps:

[0044] 1. Purification of carbon nanotubes

[0045] Place 1g of commercially available carbon nanotube sample in a muffle furnace, heat at 500℃ for 60min, then stop heating, and take out the sample after cooling to room temperature. Place the above carbon nanotube in a 250ml flask and add 70ml of 6mol / L hydrochloric acid solution, and ensure that the carbon nanotube is in full contact with the hydrochloric acid solution. Heat at 140℃ for 2h in an oil bath, then cool to room temperature, wash three times with ultrapure water by centrifugation, and freeze-dry in a freeze dryer to obtain a purified carbon nanotube sample.

[0046] 2. Oxidation of carbon nanotubes

[0047] Take 1g of the purified carbon nanotubes and put them into a 250ml round-bottom flask, add 23ml of concentrated sulfuric acid (mass concentration of about 98%), and stir at room temperature overnight; transfer the above solution to a water bath and heat it. When the temperature rises to 40°C, add 350mg of sodium nitrate; slowly add 1g of potassium permanganate while keeping the reaction temperature below 45°C; continue to stir the solution at 40°C for 30min; then add 3ml of water to the flask, and add another 3ml of water after 5min. After another 5min, add 40ml of water; after 15min, remove the flask from the water bath, add 140ml of water and 10ml of 30% mass concentration of hydrogen peroxide to terminate the reaction; wash the oxidized carbon nanotubes by repeatedly using 5% mass concentration of HCl solution and water, and then freeze-dry them to obtain oxidized carbon nanotubes.

[0048] 3. Loading of molecular catalysts

[0049] 30 mg of oxidized carbon nanotubes were ultrasonically dispersed in 20 ml of DMF for 1 h using an ultrasonic dispersion device with a power of 1800 W to obtain a CNT suspension.

[0050] 3 mg of CoPc was ultrasonically dispersed with another 10 ml of DMF and then added to the above CNT suspension, further ultrasonicated for 1 h and stirred at room temperature for 24 h. The obtained solid was separated by centrifugation and washed with DMF, ethanol and water, and freeze-dried to obtain the CO2 reduction catalyst CoPc MDE-O.

[0051] 4. Hydrophobic modification of carbon nanotubes

[0052] 1H,1H,2H,2H-perfluorodecyltriethoxysilane was used as an example to hydrophobize carbon nanotubes.

[0053] A mixed solution of ethanol and water was prepared, wherein the mass ratio of ethanol to water was 1.5:1; a 1H,1H,2H,2H-perfluorodecyltriethoxysilane solution was added to the above ethanol solution, wherein the concentration of 1H,1H,2H,2H-perfluorodecyltriethoxysilane was 3wt%, and the mixture was stirred at room temperature for 2h to promote the hydrolysis of 1H,1H,2H,2H-perfluorodecyltriethoxysilane.

[0054] CoPc MDE-O was added to the hydrolyzed 1H,1H,2H,2H-perfluorodecyltriethoxysilane solution, wherein the mass ratio of CoPc MDE-O to 1H,1H,2H,2H-perfluorodecyltriethoxysilane was 20:1, and the mixture was stirred for 2.5 h in a 48°C water bath. The suspension of CoPc MDE-O and 1H,1H,2H,2H-perfluorodecyltriethoxysilane was heated to 75°C and maintained for 15 min to graft 1H,1H,2H,2H-perfluorodecyltriethoxysilane onto the surface of CoPc MDE-O, and the grafted CoPc MDE-O was heated to boiling and maintained for 30 min to promote further grafting of silanol groups. The treated CoPc MDE-O was centrifuged and washed three times in an ethanol solution to remove the unreacted 1H,1H,2H,2H-perfluorodecyltriethoxysilane reagent and then freeze-dried to obtain the final product CoPc MDE-1.0Si-1.

[0055] The SEM image of the oxidized carbon nanotubes obtained in step 2 is shown in Figure 2 , SEM images of carbon nanotubes loaded with molecular catalysts and hydrophobically modified are shown in Figure 3 . Reference Figure 2 As shown, the diameter of the oxidized carbon nanotubes prepared in this example did not change significantly, and no obvious structural damage or deformation was observed under an electron microscope, and the original structural characteristics and morphology were maintained, proving that the carbon nanotubes maintained their structural stability during the oxidation process. Figure 3 As shown, the hydrophobically modified carbon nanotubes prepared in this example, although modified with silane, still maintain their original shape and are evenly arranged on the surface of carbon paper, and the overall structure has no obvious defects, indicating that the silane grafting process will not affect the structural characteristics of the carbon nanotubes.

[0056] Test Example 1

[0057] Preparation of CoPc MDE catalyst (comparative example): Place 1g of commercially available carbon nanotube sample in a muffle furnace, heat at 500℃ for 60min, stop heating, and take out the sample after cooling to room temperature. Place the above carbon nanotube in a 250ml flask and add 70ml volume of 6mol / L hydrochloric acid solution, and ensure that the carbon nanotube is in full contact with the hydrochloric acid solution. Use an oil bath to heat at 140℃ for 2h and then cool to room temperature. Use ultrapure water to centrifuge and wash three times and then put it into a freeze dryer to freeze-dry to obtain the purified carbon nanotube sample. The obtained 30mg carbon nanotube (not oxidized) is ultrasonically dispersed in 20ml DMF for 1h using an ultrasonic dispersion device with a power of 1800W to obtain a CNT suspension. 3mg of CoPc is ultrasonically dispersed with another 10ml DMF, then added to the above CNT suspension, further ultrasonicated for 1h and stirred at room temperature for 24h. The obtained solid is separated by centrifugation and centrifuged and washed with DMF, ethanol and water, and freeze-dried to obtain a CO2 reduction catalyst CoPc MDE.

[0058] The CoPc MDE-1.0Si-1 and CoPc MDE in Example 1 were used to prepare catalyst ink and further prepare working electrodes with a working area of ​​1 cm 2 The catalytic performance of the two catalytic electrodes, CoPc MDE-1.0Si-1 and CoPc MDE, was tested at different current densities in 1M KHCO3 solution. The specific steps are as follows:

[0059] S1. Preparation of catalyst ink

[0060] The preparation method of CoPc MDE catalyst ink is as follows: 8 mg of CoPc MDE catalyst powder is weighed and dispersed in 3.6 ml of isopropanol, and then 0.8 mg of Nafion ionomer (10 wt% of the catalyst amount, with Nafion as the catalyst amount) is added. TM Added in the form of a polymer dispersant);

[0061] The preparation method of CoPc MDE-1.0Si-1 catalyst ink is as follows: 8 mg of CoPc MDE-1.0Si-1 catalyst powder is weighed and dispersed in 3.6 ml of isopropanol, and then 0.8 mg of Nafion ionomer (10 wt% of the catalyst amount is Nafion) is added. TM Added in the form of a polymer dispersant);

[0062] S2. Preparation of working electrode

[0063] After the catalyst ink prepared in S1 was dispersed under high-power ultrasound for 1 h, the catalyst ink was loaded on YLS-30T carbon paper until the catalyst loading reached 1 mg / cm 2The loading method can be a drop coating method or a spray coating method. This embodiment adopts the drop coating method. The YLS-30T carbon paper is heated on a heating table at 40°C to promote the volatilization of isopropanol during the electrode preparation process.

[0064] The catalytic performance test results of the carbon nanotube molecular catalysts without hydrophobic modification and with hydrophobic modification at different current densities are shown in the figure. Figure 4 As shown in Figure 2, CoPc MDE-1.0Si-1 exhibits excellent catalytic performance at all current densities, and the Faradaic efficiency of CO is always maintained above 98%. In contrast, CoPc MDE has difficulty in effectively maintaining the hydrophobicity of the electrode at 150 and 200 mA / cm 2 A CO Faradaic efficiency of over 95% can be achieved at current densities of 250 mA / cm 2 Gradually increase to 350mA / cm 2 , its Faradaic efficiency gradually drops to 88%.

[0065] Test Example 2

[0066] The two working electrodes prepared in Test Example 1 were charged in 1M KHCO3 solution at a current density of 100 mA / cm 2 Conduct stability testing.

[0067] The carbon nanotube molecular catalyst without hydrophobic modification and hydrophobic modification at 100mA / cm 2 The stability test results are as follows: Figure 5 As shown. Figure 5 It can be seen that the Faraday efficiency of the CoPc MDE electrode increases rapidly, and the Faraday efficiency of CO remains above 90% only in the last 160 hours. In contrast, the Faraday efficiency of CoPc MDE-1.0Si-1 remains relatively stable throughout the test, with a test time of more than 700 hours, and the Faraday efficiency remains above 97% within 600 hours, and 95% of the Faraday efficiency can still be maintained throughout the test. This result shows that the stability of CoPc MDE-1.0Si-1 in CO2RR is significantly better than that of CoPc MDE. As mentioned above, hydrophobic modification of carbon nanotubes can greatly improve the hydrophobicity of the prepared catalyst and maintain a high degree of stability during the reaction, effectively preventing the electrolyte from entering the micro-nano pore structure of the electrode, thereby maintaining a high Faraday efficiency during a long reaction.

[0068] The good stability of catalytic electrode performance during long-term testing is crucial for CO2 reduction reactions in practical applications and has positive significance for large-scale industrial production.

[0069] Test Example 3

[0070] The effects of different CF chains in silane on the hydrophobicity of silane-modified carbon nanotube molecular catalysts were tested. Catalysts were prepared using 1H, 1H, 2H, 2H-perfluorodecyltriethoxysilane, (3,3,3-trifluoropropyl)trimethoxysilane, and hexadecyltrimethoxysilane. The specific preparation methods were the same as those in Example 1. The modified catalysts were named CoPc MDE-1.0Si-1, CoPc MDE-1.0Si-2, and CoPc MDE-1.0Si-3, respectively.

[0071] The contact angle test of different silane-modified carbon nanotube molecular catalysts was carried out using an optical contact angle meter. 3.5 μl of ultrapure water was dropped onto the catalytic electrode surface, and the software of the contact angle meter was used to analyze the contour curve of the droplet shape and calculate the contact angle between the droplet and the electrode surface. The test results are shown in Figure 2. Figure 6 As shown, the contact angles of the three electrodes are CoPc MDE-1.0-Si-1>CoPc MDE-1.0Si-2>CoPc MDE-1.0Si-3. Due to the differences in the length and content of the carbon-fluorine chains contained in different silanes, the electrodes prepared by the modified carbon nanotube molecular catalysts show different hydrophobicity. 1H,1H,2H,2H-perfluorodecyltriethoxysilane can provide a better hydrophobic environment for the catalytic electrode compared with (3,3,3-trifluoropropyl)trimethoxysilane due to its longer CF chain. In contrast, hexadecyltrimethoxysilane has lower hydrophobicity due to the lack of CF chains. This performance difference is particularly significant under high current density conditions. 1H,1H,2H,2H-perfluorodecyltriethoxysilane and (3,3,3-trifluoropropyl)trimethoxysilane containing CF chains showed excellent catalytic performance at different current densities. However, hexadecyltrimethoxysilane, which only has CH chains, could not maintain a sufficient hydrophobic environment at high current density, resulting in decreased catalytic performance. Therefore, by fine-tuning the chemical structure of the silane molecule, the hydrophobic properties of the electrode can be systematically regulated, thereby optimizing its application effect in electrocatalytic reactions.

[0072] Test Example 4

[0073] In order to test the effect of silane hydrophobic modification of carbon nanotubes with different oxidation degrees on the reaction performance, 1H, 1H, 2H, 2H-perfluorodecyltriethoxysilane was used as an example, and the catalyst was prepared by referring to the method of Example 1, but the addition amounts of sodium nitrate and potassium permanganate were adjusted, which were: 280 mg sodium nitrate, 0.8 g potassium permanganate; 350 mg sodium nitrate, 1 g potassium permanganate; 420 mg sodium nitrate, 1.2 g potassium permanganate; 490 mg sodium nitrate, 1.4 g potassium permanganate. The prepared catalysts were named CoPc MDE-0.8Si-1, CoPc MDE-1.0Si-1, CoPc MDE-1.2Si-1, and CoPc MDE-1.4Si-1, respectively; at the same time, the CoPc MDE catalyst prepared above without oxidation modification and silane grafting was used as a comparison, and its electrode preparation method was referred to Test Example 1. Increasing the degree of oxidation can introduce more hydroxyl groups on the surface of carbon nanotubes, thereby grafting more silane groups and improving the hydrophobicity of silane-modified carbon nanotubes. Excessive oxidation will damage the graphite structure of carbon nanotubes, reduce their conductivity and the loading amount of molecular catalysts, and thus affect the catalytic performance.

[0074] At 550mA / cm 2 The catalytic performance of the hydrophobically modified carbon nanotube molecular catalysts after different oxidation degrees was tested under current density. The results are as follows Figure 7 The different oxidation degrees of carbon nanotubes caused differences in the performance of the catalytic electrode. CoPc MDE-1.0Si-1 had the best performance, while CoPc MDE-1.4Si-1 had a poor performance. This may be due to the fact that excessive oxidation reduces the conductivity of carbon nanotubes, reduces the molecular catalyst loading, reduces active sites, and thus reduces the catalytic efficiency.

[0075] In this specification, each embodiment is described in a progressive manner, and each embodiment focuses on the differences from other embodiments. The same or similar parts between the embodiments can be referred to each other. For the device disclosed in the embodiment, since it corresponds to the method disclosed in the embodiment, the description is relatively simple, and the relevant parts can be referred to the method part.

[0076] The above is a detailed introduction to the carbon-fluorocarbon chain-modified carbon-based hydrophobic electrocatalytic CO2 reduction catalyst, preparation method and application provided by the present invention. Specific examples are used herein to illustrate the principles and implementation methods of the present invention. The description of the above embodiments is only used to help understand the method of the present invention and its core idea. It should be pointed out that for ordinary technicians in this technical field, without departing from the principles of the present invention, the present invention can also be improved and modified, and these improvements and modifications also fall within the scope of protection of the claims of the present invention.

Claims

1. A method for preparing a carbon-based hydrophobic electrocatalytic CO2 reduction catalyst modified by a carbon-fluorine chain, characterized in that The method comprises the following steps: S1, heating the carbon nanotubes at a temperature of 400-500°C for 0.5h-1.5h, cooling to room temperature, washing after purification by acid washing, and freeze-drying to remove impurities contained in the carbon nanotubes; S2, heating the carbon nanotubes obtained by the pretreatment in S1 in a mixed solution of concentrated sulfuric acid, sodium nitrate and potassium permanganate with a mass concentration of 96-98% to perform oxidation treatment on the carbon nanotubes to introduce hydroxyl groups, washing and freeze-drying; The oxidation treatment temperature is not higher than 45° C. S3, subjecting the oxidized carbon nanotubes obtained by the treatment in S2 to ultrasonic treatment in a DMF solvent environment to load the molecular catalyst, washing, and freeze-drying; The molecular catalyst is cobalt phthalocyanine (CoPc) or nickel phthalocyanine; S4, hydrophobically modifying the oxidized carbon nanotubes loaded with molecular catalysts in S3 by using silane in a silane aqueous solution, heating to 45°C-120°C for 2h-4h, centrifugally washing to remove unreacted reagents, and freeze-drying to obtain a carbon-fluorine chain-modified carbon-based hydrophobic electrocatalytic CO2 reduction catalyst; Preparation of silane aqueous solution: silane content is 1wt% to 10wt%, the solvent is a mixture of ethanol and water in a mass ratio of 1 to 2:1, and the silane and solvent are mixed and hydrolyzed for 1 to 6 hours; The mass ratio of the oxidized carbon nanotubes to silane is 10:1 to 60:

1.

2. The preparation method according to claim 1, characterized in that: S1, the acid washing step is to heat the carbon nanotubes in a 4-8 mol / L hydrochloric acid solution at 130-150° C. for 2 h to 3 h.

3. The preparation method according to claim 1, characterized in that: The reaction temperature of the oxidation treatment of the carbon nanotubes to introduce hydroxyl groups in S2 is 40-45°C.

4. The preparation method according to claim 1, characterized in that: The silane includes one or more of 1H, 1H, 2H, 2H-perfluorodecyltriethoxysilane, 1H, 1H, 2H, 2H-perfluorododecyltrichlorosilane, (3, 3, 3-trifluoropropyl)trimethoxysilane, 1-(trimethylsilyl)heptafluoropropane, 3, 3, 3-trifluoropropylmethyldimethoxysilane, propyltrimethoxysilane or hexadecyltrimethoxysilane.

5. The preparation method according to claim 1, characterized in that: In S4, the mixture is heated at 40-50° C. for 2-3 h, maintained at 70-80° C. for 10-20 min, and heated to boiling and maintained for 20-40 min to promote sufficient grafting of silanol groups.

6. The preparation method according to claim 1, characterized in that: The process of introducing hydroxyl groups by oxidation treatment in S2 is as follows: the carbon nanotubes obtained by purification pretreatment are stirred overnight in concentrated sulfuric acid with a mass concentration of 96-98% at room temperature; sodium nitrate is added when the above solution is heated to 40°C-45°C; potassium permanganate is slowly added while keeping the reaction temperature below 45°C; The usage ratio of carbon nanotubes: 96-98% concentrated sulfuric acid: sodium nitrate: potassium permanganate is 1g: 20ml-23ml: 280mg-420mg: 0.8g-1.2g; Then continue stirring at 40°C to 44°C, add appropriate amount of water intermittently, stop heating after the reaction is sufficient, and add appropriate amount of water and hydrogen peroxide to the system to terminate the reaction.

7. The preparation method according to claim 1, characterized in that: In S2, the oxidized carbon nanotubes are repeatedly washed with 5% by mass HCl solution and water.

8. A carbon-fluorine chain modified carbon-based hydrophobic electrocatalytic CO2 reduction catalyst as claimed in claim 1.

9. Use of the carbon-fluorochain-modified carbon-based hydrophobic electrocatalytic CO2 reduction catalyst according to claim 8 in the preparation of catalyst ink.

10. Use of the carbon-fluorine chain modified carbon-based hydrophobic electrocatalytic CO2 reduction catalyst according to claim 8 in the preparation of a working electrode.

Citation Information

Patent Citations

  • Novel nickel phthalocyanine-modified pericarp carbon framework catalyst for electrocatalytic reduction of carbon dioxide, its preparation method and application

    CN114934284A